Therapeutic potential of TNFR2 agonists: a mechanistic perspective - Chen, Yibo; Jiang, Mengmeng; Chen, Xin (Frontiers in Immunology, 2023)
TNFR2 agonists have been investigated as potential therapies for inflammatory diseases due to their ability to activate and expand immunosuppressive CD4+Foxp3+ Treg cells and myeloidderived suppressor cells (MDSCs). Despite TNFR2 being predominantly expressed in Treg cells at high levels, activated effector T cells also exhibit a certain degree of TNFR2 expression.Consequently, the role of TNFR2 signaling in coordinating immune or inflammatory responses under different pathological conditions is complex. In this review article, we analyze possible factors that may determine the therapeutic outcomes of TNFR2 agonism, including the levels of TNFR2 expression on different cell types, the biological properties of TNFR2 agonists, and disease status. Based on recent progress in the understanding of TNFR2 biology and the study of TNFR2 agonistic agents, we discuss the future direction of developing TNFR2 agonists as a therapeutic agents.